Letter (copy) - Morgan, Betty
1939-08-02 038-0076-002 295/12 H. 2nd August, 1939. Dear Mr. Leaker, Many thanks for your letter of July 28th, which I placed before the Basque Administrative Sub Committee at its last meeting. We are very grateful to the Lord Mayor for passing over to Walsall the stores remaining at Elford. With regard to your other point, we quite understand that you might like to transfer to Walsall some of the balance left from Elford, especially as some of this was collected in the Walsall area. On the other hand, we are at present contributing from Head Office to the maintenance at other homes of the chiIdren who left Elford, and we had naturally been counting on the Elford balance to help us with this particular item of expenditure. In the circumstances, the Basque Administrative Sub-committee suggests that you should transfer £50 of the Elford balance to Walsall, and send the remainder to us, to be used towards the maintenance of Elford children now in other homes. Owing to the present financial position, we should be grateful for anything you can do to expedite payment of the latter amount. Yours sincerely, Organizing Secretary. V.H. Leaker, Esq., The Lord Mayor's Parlour, The Council House, Birmingham, 1. 292/946/38/76(II)